After empire : the conceptual transformation of the Chinese state, 1885-1924 - Zarrow, Peter Gue (Stanford, Calif. : Stanford University Press, 2012)
From 1885-1924, China underwent a period of acute political struggle and cultural change, brought on by a radical change in thought: after over 2,000 years of monarchical rule, the Chinese people stopped believing in the emperor. These forty years saw the collapse of Confucian political orthodoxy and the struggle among competing definitions of modern citizenship and the state. What made it possible to suddenly imagine a world without the emperor?
Kang Youwei's philosophy of power and the 1898 reform movement -- Liang Qichao and the citizen-state -- Sovereignty and the translated state -- Voices of receding reaction -- Identity, history, and revolution -- Restoration and revolution -- Founding the Republic of China -- The last emperors.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Monarchy -- China -- History -- 20th century; China -- History -- 1861-1912.; China -- History -- 1912-1928.; China -- Politics and government -- 19th century; China -- Politics and government -- 20th century; Chine -- Histoire -- 1861-1912.; Chine -- Histoire -- 1912-1928.; Chine -- Politique et gouvernement -- 19e siècle.; Chine -- Politique et gouvernement -- 20e siècle.; HISTORY -- Asia -- China; Monarchy; Politics and government; China; 1800-1999; History